Cyberbullying Criminal Law from the Perspective of Hadith Ahmad Number 3646 and Article 27A of Law Number 1 of 2024 - Husaeni, Fakhri Gilman; Arifin, Tajul (Universitas Islam Negeri Sumatera Utara, 2025)
This research is motivated by the increasing acts of bullying in society, particularly through social media or what is commonly known as cyberbullying, which has serious impacts on victims both psychologically and socially. The purpose of this study is to analyze cyberbullying criminal law from the perspective of Hadith Ahmad 3646 and Article 27A of Law Number 1 of 2024. This type of research is a library research, where the researcher gathers information from scholarly works previously written by academics. The results of the study indicate that, based on Hadith Ahmad number 3646 and Article 27A of Law Number 1 of 2024, it is prohibited for followers to incite, gossip, use harsh language, call others with inappropriate nicknames in front of others, and engage in other actions that attack human dignity and honor. Through this study, it is expected to enhance understanding of ethics and literacy when interacting on social media.